Analysis of Public Satisfaction With Servqual and SWOT Approaches on BPOM Public Services in Pangkal Pinang - Riyanto, Agus; Azis, Anton Mulyono; Sutarman, Sutarman; Siregar, Khairani Ratnasari (The Eastasouth Management and Business, 2025)
This study aims to evaluate public satisfaction with BPOM services in Pangkal Pinang by applying the SERVQUAL method to identify the gap between expectations and perceptions, and to determine the influential service quality dimensions, both partially and simultaneously. The analysis involved five SERVQUAL dimensions—Tangibles, Reliability, Responsiveness, Assurance, and Empathy—plus an additional Anti-Corruption dimension. Using a quantitative approach and survey of 104 respondents, data were analyzed through multiple regression, t-tests, and F-tests. The findings revealed that Tangibles, Reliability, and Responsiveness had significant partial effects on public satisfaction, while Assurance and Empathy were not statistically significant. Simultaneously, all dimensions significantly influenced satisfaction, and the Customer Satisfaction Index (CSI) score of 94.00 indicated a high level of satisfaction. SWOT analysis was used to formulate strategies, with the SO (Strengths–Opportunities) strategy emerging as the most appropriate—highlighting the need to leverage internal strengths, such as digital innovation and qualified human resources, to seize external opportunities. The study concludes that while BPOM’s service quality is generally rated highly, improvements are needed in empathy and assurance aspects. Therefore, it is recommended to enhance service digitization, strengthen employee competencies and ethics, improve public communication, and expand inclusive, participatory service models.